Highly active WO3@anatase-SiO2 aerogel for solar-light-driven phenanthrene degradation: Mechanism insight and toxicity assessment - Cai, Zhengqing; Hao, Xiaodi; Xianbo Sun; Du, Penghui; Liu, Wen; Fu, Jie (Water Research, 2019)
The global energy crisis and water pollution drive the researchers to develop highly effective and less energy intensive water purification technologies. In this study, a highly active WO3@TiO2–SiO2 nanocomposite was synthesized and used for photocatalytic degradation of persistent organic pollutants under simulated solar light. The optimum WO3@TiO2–SiO2 prepared with 2 wt% WO3 loading and calcination at 800 °C exhibited higher photocatalytic activity, as the rate constant (k1) for phenanthrene degradation was ∼7.1 times of that for the commercial TiO2 (P25). The extremely large specific surface area (>400 m2/g) of WO3@TiO2–SiO2 afforded it with enlarged pollutants adsorption performance and abundant active surface sites. The heterojunction of anatase with SiO2 as well as loading of WO3 decreased the band gap energy (Eg) of TiO2, which extended the utilization spectrum of TiO2 to visible region. Formation of Ti–O–Si band indicated the excess charges can cause Brønsted acidity due to the absorption of protons to compensate the charges. Moreover, the migration of photo-excited electrons from the conduction band of anatase to WO3 and holes in the opposite direction restrained the electron-hole recombination. The photocatalytic degradation mechanism and pathway for phenanthrene degradation were proposed based on experimental analysis and density functional theory (DFT) calculation, and the toxicities of the degradation intermediates were evaluated by quantitative structure–activity relationship (QSAR) analysis. WO3@TiO2–SiO2 also showed good separation (settling) performance and high stability. Our work is expected to offer new insight into the photocatalytic mechanism for WO3, TiO2 and SiO2 based heterojunctions, and rational design and synthesis of highly efficient photocatalysts for environmental application.
Keywords: Phenanthrene; Photocatalysis; Solar light; Toxicity; WO@TiO–SiO